Mental Toughness Profile of Adult Badminton Athletes in the Training Phase - Gina Denisa Maharani; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Badminton athletes often lack psychological training, so this causes several problems such as mental toughness. To overcome this problem, mental toughness is proposed as a solution. The purpose of this study was to determine the mental toughness of adult badminton athletes in the training phase. The method used in this research is a descriptive method with a quantitative approach. The research instrument used is the Mental Toughness Inventory (MTI). The samples involved in this study were 12 badminton athletes. The results of data analysis show that adult badminton athletes have good mental toughness, whereas male athletes have better mental toughness abilities than female athletes.